2009
DOI: 10.1128/jvi.00271-09
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase G Phosphorylates Mosquito-Borne Flavivirus NS5

Abstract: Serine/threonine phosphorylation of the nonstructural protein 5 (NS5) is a conserved feature of flaviviruses, but the kinase(s) responsible and function(s) remain unknown. Mass spectrometry was used to compare the phosphorylation sites of the NS5 proteins of yellow fever virus (YFV) and dengue virus (DENV), two flaviviruses transmitted by mosquitoes. Seven DENV phosphopeptides were identified, but only one conserved phosphoacceptor site (threonine 449 in DENV) was identified in both viruses. This site is predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 23 publications
1
53
0
2
Order By: Relevance
“…A previous study demonstrated that the synthesis of negative-sense RNA primarily depends on NS5 RdRp activity, whereas the synthesis of positive-sense RNA requires multiple additional enzymatic functions from both NS3 (helicase, ATPase, RNA triphosphatase) and NS5 (guanylyltransferase, methyltransferase) (46). Although there is no evidence so far showing that PKA directly phosphorylates NS5, it has been shown that NS5 could indeed be phosphorylated at Thr 449 in the RdRp fingers domain by protein kinase G, leading to the inactivation of its function (55). The role of phosphorylation of the RdRp Thr 449 residue is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the synthesis of negative-sense RNA primarily depends on NS5 RdRp activity, whereas the synthesis of positive-sense RNA requires multiple additional enzymatic functions from both NS3 (helicase, ATPase, RNA triphosphatase) and NS5 (guanylyltransferase, methyltransferase) (46). Although there is no evidence so far showing that PKA directly phosphorylates NS5, it has been shown that NS5 could indeed be phosphorylated at Thr 449 in the RdRp fingers domain by protein kinase G, leading to the inactivation of its function (55). The role of phosphorylation of the RdRp Thr 449 residue is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…First, the changes at the identified sites might contribute to the alteration of interacting behavior between NS5 and putative function-related factors and (or) template. It has been reported that, during viral replication, the methyltransferase domains of the flavivirus NS5 proteins recruit cellular factors kinases (CK1 and PKG), 46,47 mitochondrial trifunctional protein (MTP), 48 and PSD-95/Dlg/ ZO-1 proteins, 49,50 while the RdRp domains can interact with the nuclear import receptors importin-α and importin-β, 43,51 cyclophilin A, 52 heat shock protein 70 (Hsp70), 53 protein kinase G (PKG), 40 L subunit of human eukaryotic translation initiation factor 3 (eIF3L), 54 and small nuclear ribonucleoprotein U1A. 55 These factors can enhance formation of the replication complex, RNA stability, genome translation, and/or posttranslational modification.…”
Section: Discussionmentioning
confidence: 99%
“…First, Fyn's kinase activity may regulate the function of a component of the viral replicase complex. Along these lines, it has already been shown that the DV NS5 protein is phosphorylated at multiple sites during infection (52,53) and that the NS3 protein of Japanese encephalitis virus (JEV) is likely phosphorylated by Src kinase (54). Although mutation of the serine in DV NS5 phosphorylated by protein kinase G resulted in reduced RNA replication in a replicon system (53), more work is needed to unequivocally establish the significance of these phosphorylations in flavivirus steady-state RNA replication.…”
Section: Discussionmentioning
confidence: 99%